2015
DOI: 10.1111/cei.12703
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive investigation on the distribution of circulating follicular T helper cells and B cell subsets in primary Sjögren’s syndrome and systemic lupus erythematosus

Abstract: SummaryFollicular T helper (Tfh) cells have a crucial role in regulating immune responses within secondary lymphoid follicles by directing B cell differentiation towards memory B cells and plasma cells. Because abnormal humoral responses are key features in both primary Sj€ ogren's syndrome (pSS) and systemic lupus erythematosus (SLE), the aim of this study was to profile the pathological connection between peripheral Tfh cells and B cells in the two diseases. Twenty-five pSS patients, 25 SLE patients and 21 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 45 publications
17
99
0
Order By: Relevance
“…For the identification of different lymphocyte subpopulations, PBMCs were stained then assessed using flow cytometer, as described previously [17]. For identification of B cell subsets, we used the combination of IgD-fluorescein isothiocyanate (FITC)/CD27-phycoerythrin (PE)/CD19-phycoerythrin-Cyanine dye 5 (PE-Cy5) (Beckman Coulter Inc, Fullerton, CA, USA and Immunotech, Marseille, France) and CD38-FITC/CD27-PE/CD19-PE-Cy5/CD24-allophycocyanin (APC) (BD Biosciences, San Diego, CA, USA and Beckmann Coulter and BioLegend, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the identification of different lymphocyte subpopulations, PBMCs were stained then assessed using flow cytometer, as described previously [17]. For identification of B cell subsets, we used the combination of IgD-fluorescein isothiocyanate (FITC)/CD27-phycoerythrin (PE)/CD19-phycoerythrin-Cyanine dye 5 (PE-Cy5) (Beckman Coulter Inc, Fullerton, CA, USA and Immunotech, Marseille, France) and CD38-FITC/CD27-PE/CD19-PE-Cy5/CD24-allophycocyanin (APC) (BD Biosciences, San Diego, CA, USA and Beckmann Coulter and BioLegend, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Studies evaluating the subpopulations of B cells in the peripheral blood of patients with SS have measured decreased numbers of CD27+ memory B cells [11,12,13,14]. Genetic evaluation of these cells has identified increased numbers of mutated Ig transcripts, suggesting a high percentage of the CD27+ cells are IgM memory B cells [12].…”
Section: B Cell Subpopulations In Patients With Sjogren’s Syndromementioning
confidence: 99%
“…The role of TFH cells in human SLE, in which autoantibodies are considered as primarily markers of the disease, is yet not well studied. However, it was shown that elevated frequencies of peripheral blood CD4 + CXCR5 + precursor TFH cells were accompanied by increased IL-21 levels and excessive pathogenic autoantibody production in patients with SLE [85]. Equal pathological patterns were observed in other autoimmune diseases such as juvenile dermatomyositis and Sjögren's syndrome [85].…”
Section: Tfh Cell Homeostasis-their Dysregulation Affects Various Dismentioning
confidence: 99%
“…However, it was shown that elevated frequencies of peripheral blood CD4 + CXCR5 + precursor TFH cells were accompanied by increased IL-21 levels and excessive pathogenic autoantibody production in patients with SLE [85]. Equal pathological patterns were observed in other autoimmune diseases such as juvenile dermatomyositis and Sjögren's syndrome [85]. Increased levels of memory TFH cells and plasma IL-21 were observed in patients with MS compared to healthy controls and patients with complete remission of the disease [86].…”
Section: Tfh Cell Homeostasis-their Dysregulation Affects Various Dismentioning
confidence: 99%